Awareness, Knowledge, and Practices towards Reading Snack Food Labels among Malaysian Adolescents - Md Nor, Norazmir; Mohd Rusli, Siti Farhanah; Mohd Asmawi, Ummi Mohlisi (Jurnal Gizi dan Pangan, 2023)
This study aimed to determine the awareness, knowledge, and practices regarding food labels and factors that influence their use; a cross-sectional study was conducted among 200 Malaysian adolescents aged 10 to 19. Participants completed an online Food Label Use Questionnaire (FLUQ) that included demographic, nutrition knowledge, label use, and factors affecting label use. SPSS version 28.0 was used for data analysis. The results showed that 93% of adolescents correctly identified the consequences of over-consuming calories. Still, only 84.5% performed well on the nutrition use task, struggling to interpret calorie and carbohydrate amounts in certain foods. The main reasons for not using food labels were time constraints (45.5%), unattractive or confusing labels (36%), absence of labels on certain foods (33%), lack of health concerns (32%), and insufficient knowledge (27%). However, 90.5% of adolescents were concerned about product expiration dates and often read this information. Taste and price were the main reasons for referring to food labels, while time constraints were the main barrier to their use. In conclusion, practicing reading food labels can guide adolescents in making informed decisions about their food choices and portion intake. Awareness campaigns can aid in promoting healthy habits and empowering adolescents to make the right choices for their health.